2022
DOI: 10.1080/12298093.2022.2161974
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and community structure of ectomycorrhizal mycorrhizal fungi in roots and rhizosphere soil of Abies koreana and Taxus cuspidata in Mt. Halla

Abstract: In this study, the roots and rhizosphere soil of Abies koreana and Taxus cuspidata were collected from sites at two different altitudes on Mt. Halla. Ectomycorrhizal fungi (EMF) were identified by Illumina MiSeq sequencing. The proportion of EMF from the roots was 89% in A. koreana and 69% in T. cuspidata . Among EMF in rhizosphere soils, the genus Russula was the most abundant in roots of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It was also shown that Clavulina had significantly higher proportions of the ECM fungi in the roots of A. koreana on Mt. Halla [ 23 , 82 ]. Therefore, Clavulina could be considered in future A. koreana reforestation programs to establish ECM networks between the fungus and plant in their natural habitats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also shown that Clavulina had significantly higher proportions of the ECM fungi in the roots of A. koreana on Mt. Halla [ 23 , 82 ]. Therefore, Clavulina could be considered in future A. koreana reforestation programs to establish ECM networks between the fungus and plant in their natural habitats.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Tomentella was also one of the most dominant ECM fungi in the roots of A. koreana on Mt. Halla in culture-dependent [ 23 ] and culture-independent [ 82 ] studies. Hence, it can be assumed that Tomentella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation